Conductive silver paste for ceramic device, preparation method and application
By modifying silver powder and glass powder and adding amphoteric polymer to the organic carrier, it forms a high-performance conductive silver layer in ceramic devices, solving the problems of poor conductivity, poor adhesion and many holes of the existing conductive silver paste, achieving higher conductivity and adhesion.
Patent Information
- Application Number
- CN202510104773.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing conductive silver paste has problems in application such as poor conductivity, poor adhesion after sintering and many microscopic holes, which limits its use efficiency and application range in ceramic devices.
By using modified silver powder and glass powder and adding amphoteric polymer to the organic carrier, multi-layer anionic and cationic bonding is formed between the silver powder, glass powder and the organic carrier, and uniformly dispersed in the three-dimensional multi-layer ionic bonding network structure to achieve in-situ recombination of silver powder and glass powder.
It significantly improves the conductivity, adhesion and compactness of the conductive silver layer, solves the problems of poor conductivity, poor adhesion and many holes, and improves the overall performance of ceramic devices.
Smart Images

Figure CN119889763A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive paste preparation, and in particular to a conductive silver paste for ceramic devices, a preparation method and an application thereof. Background Art
[0002] Conductive silver paste is a conductive paste filled with silver powder as a conductive filler. It plays a key role in the manufacture of electronic components, photovoltaic cells and other devices, especially in the manufacture of ceramic electronic components. Silver is considered to be the best choice for electrode materials for ceramic devices because of its strong current-carrying capacity, thermal expansion coefficient close to that of ceramic blanks, good thermal stability, flexible and controllable construction process, and the ability to directly weld signal structures on the silver layer. However, the material properties and matching of the conductive silver paste itself, as well as the influence of functional additives on device performance are very significant. In addition, with the development of domestic 5G technology and photovoltaic fields, the demand for devices is increasing, and the requirements for device size, weight, heat generation and other performance are also increasing. As a result, the demand for conductive silver paste is also increasing, and higher requirements are also placed on the performance of conductive silver paste. Although, in China, the production scale of the market for conductive silver paste and its upstream silver powder has gradually expanded, and a certain degree of industrialization has been formed in the industry; and the market share of domestic conductive silver paste is increasing; however, compared with imported conductive silver paste products, domestic conductive silver paste still has certain deficiencies in quality. When domestic conductive silver paste is used, there is poor interface between organic and inorganic raw materials, which leads to poor conductivity, high dielectric loss, many pores and poor adhesion after sintering. It is difficult to achieve coordinated improvement of conductivity and adhesion, which limits the use efficiency and application scope of conductive silver paste. Therefore, research on a high-performance conductive silver paste is of great significance to the performance improvement of devices and the development of communication technology.
[0003] The invention provides a conductive silver paste for ceramic devices, a preparation method and an application thereof, so as to solve the problems existing in the prior art such as poor conductivity, poor adhesion after sintering and a large number of microscopic holes of the existing conductive silver paste. Summary of the invention
[0004] The purpose of the present invention is to provide a conductive silver paste for ceramic devices, a preparation method and an application thereof, so as to solve the problems existing in the prior art such as poor conductivity, poor adhesion after sintering and a large number of microscopic holes of the existing conductive silver paste.
[0005] The technical solution of the present invention is: a method for preparing a conductive silver paste for ceramic devices, wherein the conductive silver paste comprises 60-85 parts of modified silver powder, 1-6 parts of modified glass powder, 13-24 parts of organic carrier, and 1 part of an auxiliary agent, calculated by weight; the auxiliary agent comprises at least one of copper oxide and zinc oxide;
[0006] The preparation method of the conductive silver paste comprises the following steps:
[0007] S1, weighing nanocellulose and silver powder respectively, and first preparing the weighed nanocellulose to form a 0.3%-5% nanocellulose dispersion, and then adding the weighed silver powder to the nanocellulose dispersion, and then heating to 40° C.-60° C. to react the nanocellulose and the silver powder, and after reacting for 0.5 h-3 h, vacuum filtration treatment, drying treatment and grinding treatment are performed to obtain modified silver powder;
[0008] S2, respectively weighing glass powder, tris(hydroxymethyl)aminomethane and dopamine, first adding the weighed glass powder into deionized water and performing ultrasonic treatment to form a first suspension, then dissolving the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water and adding them to the first suspension, mixing them evenly to form a second suspension, then adjusting the pH value to within the range of 8-9, and rinsing after stirring for 5-24 hours to obtain a modified glass powder wrapped with polydopamine;
[0009] S3, weighing terpineol, butyl diglycol, butyl diglycol acetate, ethyl cellulose + modified chitosan, lecithin, and dimethyl phthalate in proportion, and adding them to a reactor, first heating the reactor to 60-70° C., then stirring at 200-500 r / min for 0.5-1 h, and then standing at room temperature for more than 5 hours to obtain an organic carrier;
[0010] S4, weighing the additive, the modified silver powder, the modified glass powder and the organic carrier prepared above in proportion, and adding the weighed additive, the modified silver powder and the modified glass powder into a reactor, dispersing them at 300-500r / min for 5min-10min, then adding the weighed organic carrier into the reactor, and stirring at 1000-2000r / min for 1h-4h to obtain a coarse conductive silver paste;
[0011] S5. Grind the obtained crude conductive silver paste, filter the discharged material, adjust the viscosity to 50 Pa.s-150 Pa.s, stir evenly, and obtain the conductive silver paste.
[0012] Preferably, the silver powder is a combination of submicron silver powder and micron silver powder, and the ratio of submicron silver powder to micron silver powder is 1:(1-4);
[0013] The particle size of submicron silver powder is 0.3um-1um; the particle size of micron silver powder is 1-5um.
[0014] Preferably, in step S1, the nanocellulose is any one or more of Tempo-oxidized nanocellulose, carboxymethyl nanocellulose, and carboxyethyl nanocellulose.
[0015] Preferably, in step S2, the glass powder is a combination of aluminosilicate bismuth glass powder and aluminosilicate borosilicate glass powder, and the ratio of aluminosilicate bismuth glass powder to aluminosilicate glass powder is 1:3-3:1;
[0016] The particle sizes of the aluminosilicate bismuth glass powder and the aluminoborosilicate glass powder are both 0.5-8 um.
[0017] Preferably, in the second suspension, the concentration of tris(hydroxymethyl)aminomethane is 5-10 mmol / L, and the concentration of dopamine is 1-5 g / L.
[0018] Preferably, in step S3, the ratio of the terpineol, the diethylene glycol butyl ether, the diethylene glycol butyl ether acetate, the ethyl cellulose+modified chitosan, the lecithin and the dimethyl phthalate is 27:27:27:12:4:3.
[0019] Preferably, in the ethyl cellulose + modified chitosan, the ratio of ethyl cellulose to modified chitosan is 1:(1-2);
[0020] The modified chitosan is one of carboxymethyl chitosan and carboxyethyl chitosan or a combination of the two with an acid value of 30% to 60%.
[0021] Preferably, the particle sizes of the copper oxide and the zinc oxide are both 0.5um-5um.
[0022] The invention also provides a conductive silver paste for ceramic devices, and the conductive silver paste is prepared by the above-mentioned preparation method.
[0023] The invention also provides application of the conductive silver paste in ceramic electronic devices.
[0024] Compared with the prior art, the advantages of the present invention are:
[0025] (1) The present invention provides a conductive silver paste for ceramic devices, a preparation method and an application thereof. By using modified silver powder and glass powder and adding an amphoteric polymer to an organic carrier, multi-level anionic and cationic bonds can be formed between the silver powder, glass powder and the organic carrier, so that the silver powder and glass powder can be evenly dispersed in a three-dimensional multi-level ion-bonded network structure and in-situ compounded during sintering, so that a silver conductive layer with good density, high adhesion, high conductivity and good solderability can be formed on the surface of the ceramic device; the problems of poor conductivity, poor adhesion after sintering and a large number of microscopic holes in the existing conductive silver paste in the prior art are solved.
[0026] (2) The present invention provides a conductive silver paste for ceramic devices, a preparation method and an application thereof. In the conductive silver paste, silver powder is modified by nanocellulose to obtain a modified silver powder with anionic groups uniformly distributed on the surface; glass powder is treated with tris(hydroxymethyl)aminomethane and dopamine to form hydroxyl and amino groups on the surface of the glass powder that can bind to anions; 30%-60% of carboxymethyl chitosan or carboxyethyl chitosan is added to the organic carrier to provide amphoteric ionic groups; thus, multi-level anionic and cationic bonds can be formed between the silver powder, the glass powder and the organic carrier, so that the silver powder and the glass powder can be uniformly dispersed in a three-dimensional multi-level ionic bonded network structure, and in situ compounding is performed in the three-dimensional network during sintering to obtain a more complete conductive network structure; this helps to improve the conductive performance of the conductive silver layer and the uniformity of the overall finished product; at the same time, two types of glass powder with melting points are used in the formula system, so that the glass powder can be softened and melted successively during the sintering process, which helps to form a denser conductive silver layer and improve the adhesion and conductive performance of the conductive silver layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0028] Figure 1 This is a SEM image of a conductive silver layer formed by the conductive silver paste prepared in Example 1 of the present invention after screen printing and sintering;
[0029] Figure 2 This is a SEM image of a conductive silver layer formed by the conductive silver paste prepared in Comparative Example 1 of the present invention after screen printing and sintering. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments:
[0031] The present application provides a method for preparing a conductive silver paste for ceramic devices. The conductive silver paste comprises, by weight, 60-85 parts of modified silver powder, 1-6 parts of modified glass powder, 13-24 parts of an organic carrier, and 1 part of an auxiliary agent;
[0032] The preparation method of the conductive silver paste specifically comprises the following steps:
[0033] S1. Weigh nanocellulose and silver powder respectively in a certain proportion, prepare the weighed nanocellulose with deionized water or other solvents to form a 0.3%-5% nanocellulose dispersion, and then add the weighed silver powder to the nanocellulose dispersion; then, raise the temperature of the nanocellulose dispersion to 40°C-60°C to allow the nanocellulose in the dispersion to react with the silver powder; stop the reaction after 0.5h-3h of reaction, perform vacuum filtration on the dispersion to obtain solid particles, and place the solid particles in a drying instrument for drying, and after drying, grind them to obtain modified silver powder. The nanocellulose is one or more of Tempo oxidized nanocellulose, carboxymethyl nanocellulose, carboxyethyl nanocellulose, etc.; the silver powder is submicron silver powder, micron silver powder, or a combination of submicron silver powder and micron silver powder; the particle size of the submicron silver powder is 0.3um-1um, and the particle size of the micron silver powder is 1-5um; when the combination of submicron silver powder and micron silver powder is selected, the ratio of submicron silver powder to micron silver powder is 1:(1-4).
[0034] S2. Weigh glass powder, tris(hydroxymethyl)aminomethane and dopamine in proportion, add the weighed glass powder into deionized water and perform ultrasonic treatment to form a first suspension, then dissolve the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water and add them to the first suspension, mix well to form a second suspension; then adjust the pH value of the second suspension to within the range of 8-9, stir for 5-24 hours at room temperature using a magnetic stirring instrument, then rinse until the washing liquid is colorless to obtain modified glass powder coated with polydopamine. Among them, the main components of the glass powder are silicon aluminum bismuth glass powder, aluminum borosilicate glass powder or a combination of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder, and when the main components of the glass powder are a combination of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder, the ratio between the silicon aluminum bismuth glass powder and the aluminum borosilicate glass powder is 1:3-3:1; the melting point of the silicon aluminum bismuth glass powder is in the range of 600-650°C, and the melting point of the aluminum borosilicate glass powder is in the range of 450-500°C; the particle size of the silicon aluminum bismuth glass powder and the aluminum borosilicate glass powder needs to be controlled in the range of 0.5-8um. In the second suspension, the concentration of trishydroxymethylaminomethane needs to be controlled in the range of 5-10mmo l / L, and the concentration of dopamine needs to be controlled in the range of 1-5g / L.
[0035] S3. Weigh pinene alcohol, butyl diglycol, butyl diglycol acetate, ethyl cellulose + modified chitosan, lecithin, and dimethyl phthalate in proportion, and add them to a reactor. Then, raise the temperature in the reactor to 60-70°C and stir at 200-500r / min for 0.5-1h. Then, take out, seal, and let stand at room temperature for more than 5 hours to obtain an organic carrier. In the organic carrier, the mass percentages of pineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, ethyl cellulose + modified chitosan, lecithin and dimethyl phthalate are 27:27:27:12:4:3; in the combination of ethyl cellulose + modified chitosan, the ratio of ethyl cellulose to modified chitosan is 1:(1-2); wherein, the modified chitosan can be selected from one or both of carboxymethyl chitosan and carboxyethyl chitosan with an acid value of 30%-60%.
[0036] S4. Weigh the additives and the modified silver powder, modified glass powder and organic carrier prepared as above in proportion, and add the weighed additives, modified silver powder and modified glass powder into a reactor. First disperse them at 300-500r / min for 5-10min, then add the weighed organic carrier into the reactor and increase the stirring rate to 1000-2000r / min. Stir for 1h-4h to obtain a coarse slurry of conductive silver paste. The additives include at least one of copper oxide and zinc oxide. The particle sizes of copper oxide and zinc oxide need to be controlled within the range of 0.5-5um.
[0037] S5. Firstly grind the obtained coarse conductive silver paste, adjust the roller distance during the grinding process to ensure that the fineness of the slurry after grinding is less than 10um, and then filter the ground slurry. After that, adjust the viscosity of the slurry to 50Pa.s-150Pa.s, and stir it thoroughly until it is uniform to obtain the conductive silver paste.
[0038] The present application also provides a conductive silver paste for ceramic devices, which is prepared by the above method. In addition, the present application also provides an application of the conductive silver paste in ceramic electronic devices; a specific application method of one application includes the following steps:
[0039] Step 1: Use alcohol to wipe the scraper, 250-400 mesh screen, barium titanate or magnesium titanate ceramic substrate clean; stick the screen after the alcohol evaporates on the substrate, and place the substrate on the operating table; then, pour the above conductive silver paste on the screen; then hold the angle of the scraper to the screen at 45° and pull the scraper from top to bottom slowly and forcefully so that the silver paste can evenly cover the screen pattern; after screen printing is completed, the sample needs to be left to level for 3-10 minutes; then, put the substrate sample into a 100-150℃ drying oven for drying, and the drying time is controlled to be 15-30 minutes; the conductive silver paste will solidify during the drying process; leveling can make the screen brush marks on the electrode disappear and make the electrode surface smooth.
[0040] Step 2: Place the dried and solidified substrate sample into a muffle furnace or a tube furnace in a hollow atmosphere for sintering; the sintering conditions are: a peak temperature of 750-900°C (heating at 5-8°C / min, and keeping at the peak temperature for 10 minutes); after sintering, cool to room temperature with the furnace to obtain a ceramic substrate with a conductive silver paste on the surface.
[0041] Example 1
[0042] S1. Weigh Tempo oxidized nanocellulose and a combination of submicron silver powder and micron silver powder in a ratio of 1:1 respectively, and first prepare the weighed Tempo oxidized nanocellulose to form a 0.3% Tempo oxidized nanocellulose dispersion, then add the weighed submicron silver powder and micron silver powder into the Tempo oxidized nanocellulose dispersion, then raise the temperature to 40° C. to react the Tempo oxidized nanocellulose with the combination of submicron silver powder and micron silver powder, and after reacting for 0.5 h, perform vacuum filtration treatment, drying treatment and grinding treatment to obtain modified silver powder.
[0043] S2. Weigh a combination of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder in a ratio of 1:3 as glass powder, and weigh tris(hydroxymethyl)aminomethane and dopamine at the same time. First, add the weighed glass powder into deionized water and perform ultrasonic treatment to form a first suspension; then, dissolve the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water respectively and add them to the first suspension, mix well to form a second suspension, and the concentration of tris(hydroxymethyl)aminomethane in the second suspension is 5 mmol / L, and the concentration of dopamine is 1 g / L. Then, adjust the pH value of the second suspension to within the range of 8-9, stir at room temperature for 5 hours, and then rinse until the washing liquid is colorless to obtain modified glass powder wrapped with polydopamine; wherein the particle size of the silicon aluminum bismuth glass powder and the aluminum borosilicate glass powder is 0.5-3 um.
[0044] S3. Weigh pinene alcohol, butyl diglycol, butyl diglycol acetate, ethyl cellulose in a ratio of 1:1 + carboxymethyl chitosan with an acid value of 30%, lecithin, and dimethyl phthalate in a ratio of 27:27:27:12:4:3, respectively, and add them to a reactor. First, heat the reactor to 60°C, stir at 300 r / min for 0.5 h, and then let it stand at room temperature for 5 hours to obtain an organic carrier.
[0045] S4. Weigh 1 part of copper oxide with a particle size of 0.5 um, 60 parts of modified silver powder prepared as above, 6 parts of modified glass powder, and 24 parts of organic carrier respectively by mass, and add the weighed additives, modified silver powder and modified glass powder into the reactor, disperse them at 300 r / min for 5 minutes, then add the weighed organic carrier into the reactor and increase the stirring rate to 1000 r / min, stir for 2 hours, and obtain a coarse slurry of conductive silver paste.
[0046] S5. Grind the obtained conductive silver paste to ensure that the fineness of the paste after grinding is less than 10um, filter the material, and then adjust the viscosity to 50Pa.s, and stir evenly to obtain a conductive silver paste. In this embodiment and the following embodiments, the particle size of the submicron silver powder is 0.3um-1um; the particle size of the micron silver powder is 1-5um; the melting point of the silicon aluminum bismuth glass powder is 600-650℃; the melting point of the borosilicate aluminum glass powder is 450-500℃.
[0047] Example 2
[0048] S1. Weigh a combination of Tempo oxidized nanocellulose and carboxymethyl nanocellulose in a mass ratio of 1:1 and a combination of submicron silver powder and micron silver powder in a mass ratio of 1:2 respectively, and first prepare a 2% dispersion with the weighed combination of Tempo oxidized nanocellulose and carboxymethyl nanocellulose, and then add the weighed combination of submicron silver powder and micron silver powder into the dispersion, and then raise the temperature to 60° C. to react the combination of Tempo oxidized nanocellulose and carboxymethyl nanocellulose with the combination of submicron silver powder and micron silver powder, and after reacting for 3 hours, perform vacuum filtration treatment, drying treatment and grinding treatment to obtain modified silver powder.
[0049] S2. Weigh a combination of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder in a ratio of 3:1 as glass powder, and weigh tris(hydroxymethyl)aminomethane and dopamine at the same time. First, add the weighed glass powder into deionized water and perform ultrasonic treatment to form a first suspension; then dissolve the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water respectively and add them to the first suspension, mix well to form a second suspension, and the concentration of tris(hydroxymethyl)aminomethane in the second suspension is 10 mmol / L and the concentration of dopamine is 5 g / L. Then, adjust the pH value of the second suspension to within the range of 8-9, stir at room temperature for 24 hours, and then rinse until the washing liquid is colorless to obtain modified glass powder wrapped with polydopamine; wherein the particle size of the silicon aluminum bismuth glass powder and the aluminum borosilicate glass powder is 3-5 um.
[0050] S3. Weigh pineol, butyl diglycol, butyl diglycol acetate, ethyl cellulose in a ratio of 1:2 + carboxyethyl chitosan with an acid value of 60%, lecithin, and dimethyl phthalate in a ratio of 27:27:27:12:4:3, respectively, and add them to a reactor. First, heat the reactor to 70°C, stir at 500r / min for 1h, and then let it stand at room temperature for 5 hours to obtain an organic carrier.
[0051] S4. Weigh 1 part of zinc oxide with a particle size of 3um, 85 parts of modified silver powder prepared above, 1 part of modified glass powder, and 13 parts of organic carrier respectively by mass, and add the weighed additives, modified silver powder, and modified glass powder into the reactor, disperse them at 500r / min for 5 minutes, then add the weighed organic carrier into the reactor and increase the stirring rate to 2000r / min, stir for 4h, and obtain a coarse slurry of conductive silver paste.
[0052] S5. Grind the obtained coarse conductive silver paste to ensure that the fineness of the paste after grinding is less than 10 um, filter the material, and then adjust the viscosity to 95 Pa.s and stir evenly to obtain the conductive silver paste.
[0053] Example 3
[0054] S1. Weigh carboxyethyl nanocellulose, and a combination of submicron silver powder and micron silver powder in a ratio of 1:2 respectively, and first prepare the weighed carboxyethyl nanocellulose to form a 5% dispersion, then add the weighed submicron silver powder and micron silver powder into the dispersion, then heat to 50° C. to react the carboxyethyl nanocellulose with the combination of submicron silver powder and micron silver powder, and after reacting for 3 hours, perform vacuum filtration, drying and grinding to obtain modified silver powder.
[0055] S2. Weigh a combination of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder in a ratio of 1:1 as glass powder, and weigh tris(hydroxymethyl)aminomethane and dopamine at the same time. First, add the weighed glass powder into deionized water and perform ultrasonic treatment to form a first suspension; then dissolve the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water respectively and add them to the first suspension, mix well to form a second suspension, and the concentration of tris(hydroxymethyl)aminomethane in the second suspension is 7 mmol / L and the concentration of dopamine is 3 g / L. Then, adjust the pH value of the second suspension to within the range of 8-9, stir at room temperature for 12 hours, and then rinse until the washing liquid is colorless to obtain modified glass powder wrapped with polydopamine; wherein the particle sizes of silicon aluminum bismuth glass powder and aluminum borosilicate glass powder are both 5-8 um.
[0056] S3. Weigh pineol, butyl diglycol, butyl diglycol acetate, ethyl cellulose in a ratio of 1:1.5 + carboxymethyl chitosan with an acid value of 40%, lecithin, and dimethyl phthalate in a ratio of 27:27:27:12:4:3, respectively, and add them to a reactor. First, heat the reactor to 65°C, stir at 400 r / min for 0.5 h, and then let it stand at room temperature for 5 hours to obtain an organic carrier.
[0057] S4. Weigh 1 part of a combination of copper oxide and zinc oxide in a weight ratio of 1:1, 75 parts of modified silver powder prepared above, 2.5 parts of modified glass powder, and 21.5 parts of organic carrier respectively by mass, and add the weighed additives, modified silver powder, and modified glass powder into a reactor, disperse them at 300 r / min for 8 minutes, then add the weighed organic carrier into the reactor and increase the stirring rate to 2000 r / min, stir for 2 hours, and obtain a coarse slurry of conductive silver paste; wherein the particle size of copper oxide and zinc oxide is 1um-3um.
[0058] S5. Grind the obtained coarse conductive silver paste to ensure that the fineness of the paste after grinding is less than 10 um, filter the material, and then adjust the viscosity to 150 Pa.s and stir evenly to obtain the conductive silver paste.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that the silver powder is not modified.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that the glass powder is not modified.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 1 is that no modified chitosan is used in the organic carrier.
[0065] Comparative Example 4
[0066] The difference between this comparative example and Example 3 is that the glass powder is silicon aluminum bismuth glass powder with a melting point of 600-650° C. and a particle size of 3-5 um.
[0067] Comparative Example 5
[0068] The difference between this comparative example and Example 3 is that the glass powder is borosilicate aluminum glass powder with a melting point of 450-500° C. and a particle size of 3-5 um.
[0069] The conductive silver pastes prepared in Examples 1-3 and Comparative Examples 1-5 were screen printed and sintered, and performance tests such as resistance, adhesion and morphology were performed. The test results are shown in Table 1.
[0070]
[0071] The conductive silver pastes prepared in Examples 1-3 are compared with the conductive silver pastes prepared in Comparative Examples 1-5. From the data recorded in Table 1, it can be seen that the conductive silver layer formed by the conductive silver pastes prepared in Examples 1-3 after screen printing and sintering has better density, significantly lower resistance, and significantly higher adhesion; and the morphology of the conductive silver paste prepared in Example 1 after screen printing and sintering is compared with the morphology of the conductive silver paste prepared in Comparative Example 1 after screen printing and sintering. Figure 1 , Figure 2 As shown, the conductive silver layer formed by the conductive silver paste prepared in Example 1 after screen printing and sintering has very few voids on its surface, and the hole diameter is also very small, with higher uniformity and density; while the silver layer formed by the conductive silver paste prepared in Comparative Example 1 after screen printing and sintering has more tiny holes on its surface, and the diameter of the holes is above 3um; further illustrating the formula system provided by the present application, by modifying the silver powder and glass powder and adding amphoteric polymers to the organic carrier, multi-level anionic and cationic bonds can be formed between the silver powder, glass powder and the organic carrier, and the silver powder and glass powder can be uniformly dispersed in a three-dimensional multi-level ionic bonded network structure, and the silver powder and glass powder in the three-dimensional network can be in-situ compounded during sintering, so that the obtained conductive network structure is more perfect.
[0072] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the scope of protection of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention.
Claims
1. A method for preparing a conductive silver paste for ceramic devices, characterized in that: Calculated by weight, the conductive silver paste includes 60-85 parts of modified silver powder, 1-6 parts of modified glass powder, 13-24 parts of organic carrier, and 1 part of auxiliary agent; the auxiliary agent includes at least one of copper oxide and zinc oxide; The preparation method of the conductive silver paste comprises the following steps: S1, weighing nanocellulose and silver powder respectively, and first preparing the weighed nanocellulose to form a 0.3%-5% nanocellulose dispersion, and then adding the weighed silver powder to the nanocellulose dispersion, and then heating to 40° C.-60° C. to react the nanocellulose and the silver powder, and after reacting for 0.5 h-3 h, vacuum filtration treatment, drying treatment and grinding treatment are performed to obtain modified silver powder; S2, respectively weighing glass powder, tris(hydroxymethyl)aminomethane and dopamine, first adding the weighed glass powder into deionized water and performing ultrasonic treatment to form a first suspension, then dissolving the weighed tris(hydroxymethyl)aminomethane and dopamine in deionized water and adding them to the first suspension, mixing them evenly to form a second suspension, then adjusting the pH value to within the range of 8-9, and rinsing after stirring for 5-24 hours to obtain a modified glass powder wrapped with polydopamine; S3, weighing terpineol, butyl diglycol, butyl diglycol acetate, ethyl cellulose + modified chitosan, lecithin, and dimethyl phthalate in proportion, and adding them to a reactor, first heating the reactor to 60-70° C., then stirring at 200-500 r / min for 0.5-1 h, and then standing at room temperature for more than 5 hours to obtain an organic carrier; S4, weighing the additive, the modified silver powder, the modified glass powder and the organic carrier prepared above in proportion, and adding the weighed additive, the modified silver powder and the modified glass powder into a reactor, dispersing them at 300-500r / min for 5min-10min, then adding the weighed organic carrier into the reactor, and stirring at 1000-2000r / min for 1h-4h to obtain a coarse conductive silver paste; S5. Grind the obtained crude conductive silver paste, filter the discharged material, adjust the viscosity to 50 Pa.s-150 Pa.s, stir evenly, and obtain the conductive silver paste.
2. The conductive silver paste for ceramic components according to claim 1, characterized in that: In step S1, the silver powder is a combination of submicron silver powder and micron silver powder, and the ratio of submicron silver powder to micron silver powder is 1:(1-4); The particle size of submicron silver powder is 0.3um-1um; the particle size of micron silver powder is 1-5um.
3. The conductive silver paste for ceramic components according to claim 2, characterized in that: In step S1, the nanocellulose is any one or more of Tempo-oxidized nanocellulose, carboxymethyl nanocellulose, and carboxyethyl nanocellulose.
4. The conductive silver paste for ceramic components according to claim 2, characterized in that: In step S2, the glass powder is a combination of aluminosilicate bismuth glass powder and aluminosilicate borosilicate glass powder, and the ratio of aluminosilicate bismuth glass powder to aluminosilicate glass powder is 1:3-3:1; The particle sizes of the aluminosilicate bismuth glass powder and the aluminoborosilicate glass powder are both 0.5-8 um.
5. The conductive silver paste for ceramic components according to claim 2, characterized in that: In the second suspension, the concentration of tris(hydroxymethyl)aminomethane is 5-10 mmol / L, and the concentration of dopamine is 1-5 g / L.
6. The conductive silver paste for ceramic components according to claim 2, characterized in that: In step S3, the ratio of the pineol, the diethylene glycol butyl ether, the diethylene glycol butyl ether acetate, the ethyl cellulose+modified chitosan, the lecithin and the dimethyl phthalate is 27:27:27:12:4:
3.
7. The conductive silver paste for ceramic components according to claim 2, characterized in that: In the ethyl cellulose + modified chitosan, the ratio of ethyl cellulose to modified chitosan is 1:(1-2); The modified chitosan is one of carboxymethyl chitosan and carboxyethyl chitosan or a combination of the two with an acid value of 30% to 60%.
8. The conductive silver paste for ceramic components according to claim 2, characterized in that: The particle sizes of the copper oxide and the zinc oxide are both 0.5um-5um.
9. A conductive silver paste for ceramic devices, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Use of the conductive silver paste for ceramic devices according to claim 9 in ceramic electronic devices.